Axiological approach in financial law (review of the conference "Axiology in the financial law of Central and Eastern Europe", Grodno, September 19-20, 2019) - Kirill V. Maslov (Pravoprimenenie, 2020)
The report on the speeches of the participants of the scientific conference "Axiology in the financial law of Central and Eastern Europe" is presented in the article. The conference was organized by Yanka Kupala State University of Grodno and Center for Public Finance of Central and Eastern Europe and took place in Grodno on September, 19-20, 2019. The most relevant topics were: the essence of legal values, constitutional basis of financial law, axiological approach to budgetary system, fiscal federalism, taxation of cross-border trans-actions, tax security.